Entisol Chemical Properties In The Organic Agriculture System - Viola Whit (GoAcademica Research & Publishing, 2022)
Farming systems based on high input energy materials (fossil materials), such as chemical fertilizers and pesticides, can damage soil properties and will ultimately reduce soil productivity in the future. Alternative agricultural systems using low input energy (LEE) are believed to be able to maintain soil fertility and environmental sustainability while at the same time maintaining or increasing soil productivity. Organic farming systems prioritize the use of organic materials and the recycling of waste. This research reveals how changes have occurred in the physical and chemical properties of soils that have carried out organic farming systems several times. The study uses a method of sampling farmers' land that has been studied to treat organic and non-organic farming systems. Two soil samples were taken from 2 different locations to represent organic soil farming systems and 4 soil samples were taken from 4 different locations to represent non-organic farming systems. Soil sampling was carried out at a depth of 20 cm. The results showed significant differences in the chemical properties of the soil (CEC, pH H2O, available P, available K, total N, carbon content, humic acid and fulfat) between the soil with organic and inorganic agriculture systems that showed better values ​​in the organic farming system